A study on manpower issues and productivity in warehouses and distribution centres - Wong, Yue Ying (2014)
The government has in recent years introduced several schemes for Small-and-Medium Enterprises (SMEs) in lieu of the tighter foreign labour restriction. These schemes aim to increase the productivity of companies in terms of training and improving operations’ efficiency.